Effect of weaning ration on reproductive phenomena in beef cows on range - Kiracofe, G.H.; Schalles, R.R.; Marion, G.B. (Kansas State University. Agricultural Experiment Station, 2011)
Data are available to indicate proper wintering rations for beef cows under dry lot conditions, but few are available under range management for Kansas. This is our first attempt to determine adequate winter rations for reproductive efficiency in Kansas and to notice reproductive inefficiencies for future study.
Keywords: Beef; Winter ration; Reproductive efficiency; Bluestem pasture; Alfalfa hay